Self-cleaning coating as well as preparation method and application thereof

By synthesizing SiO2-TiO2 nanoparticles with different particle sizes and improving the surface structure of TiO2, a self-cleaning coating for photovoltaic cover glass was developed, which solved the shortcomings in the preparation and performance of the existing coatings and achieved excellent self-cleaning and anti-fouling properties.

CN119592183APending Publication Date: 2025-03-11ANHUI CSG NEW ENERGY MATERIALS TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411709533.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing self-cleaning coatings cannot meet the actual use needs due to complex preparation process, small preparation area, poor mechanical properties, and poor oil-resistant pollutants.

Method used

By synthesizing SiO2-TiO2 nanoparticles with different particle sizes, a uniform coating on photovoltaic cover glass was developed, and the particle size of TiO2 nanoparticles was controlled by ethylene glycol, which increased light transmittance and film hardness, and improved the surface structure and dispersion of TiO2 by adding aniline and sodium fluoride.

Benefits of technology

Excellent self-cleaning, thermal stability, antifouling performance and good chemical and mechanical properties are achieved, and the adhesion and photocatalytic degradation efficiency of the coating are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155772610000071
    Figure BDA0005155772610000071
Patent Text Reader

Abstract

The invention discloses a self-cleaning coating as well as a preparation method and application thereof. The preparation raw materials of an antireflection film comprise tetraethoxysilane, trimethylethoxysilane, methyltrichlorosilane and water; the volume ratio of the tetraethoxysilane to the trimethylethoxysilane to the methyltrichlorosilane is 1: 1: (0.02-0.12). The surface of the cover plate glass is coated with the transparent hydrophobic anti-reflection film, dust cannot be accumulated on the surface and cannot be accumulated due to rolled spots, and therefore the dust can be easily cleaned away by wind or a small amount of rainwater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic product applications, and specifically to a self-cleaning coating and a preparation method and application thereof. Background Art

[0002] Self-cleaning coatings can automatically remove surface pollutants or dust particles under the action of external forces such as gravity, rain, and wind, or remove them through photocatalytic degradation. They have the advantages of water saving, energy saving, and environmental protection. They have important application prospects in industries such as construction, transportation, and new energy. In recent years, they have become one of the research hotspots of advanced functional coatings. At present, two types of self-cleaning coatings have been developed based on different self-cleaning principles. One type is a super-hydrophobic self-cleaning coating, which removes dust by rolling water droplets to achieve a self-cleaning function similar to that of lotus leaves. However, the existing super-hydrophobic coatings still have problems such as complex preparation process, small preparation area, poor mechanical properties, and poor resistance to oil pollutants, and lack practical use value; the other type is a self-cleaning coating based on inorganic photocatalytic semiconductor materials. Among this type of self-cleaning coating, the most typical one is titanium dioxide coating material. There are a large number of studies in the literature reporting that photoinduced super-hydrophilicity is because the photocatalytic surface has bridging oxygen. When excited by ultraviolet light, active oxygen free radicals are generated on the surface, which can react with holes to generate oxygen holes. At the same time, water is adsorbed in the oxygen vacancies to become chemically adsorbed water, forming uniformly distributed nanoscale hydrophilic micro-regions on the surface, leading to the formation of a hydrophilic surface. However, the hydroxyl groups they produce are not as stable as the bridging oxygen. When the light is stopped, the chemically adsorbed hydroxyl groups are replaced by oxygen in the air and return to a hydrophobic state. Take TiO2 photoinduced super hydrophilic film as an example: When sunlight irradiates TiO2 film, electrons are excited to form highly active electrons (e - ), and at the same time, a positively charged hole (h + ), that is, electron-hole pairs, at this time the holes can adsorb -OH to produce a hydrophilic micro-area to achieve the purpose of super-hydrophilicity. 4+ Photoreduction to Ti 3+The main reason for its super hydrophilicity is that the TiO2 coating has high light transmittance and hydrophilicity. Under ultraviolet irradiation, it generates electron-hole pairs, which then undergo redox reactions with the adsorbed on the surface of the material to generate oxygen-oxygen free radicals. The oxygen-oxygen free radicals are very active and can decompose organic pollutants to achieve surface self-cleaning. In addition, it can be converted into a super-amphiphilic surface under light, so that pollutants are in close contact with the surface, improving the efficiency of photocatalytic decomposition, and also facilitating the flushing of pollutants by rainwater to achieve surface self-cleaning. Due to the combined effect of these two self-cleaning principles, the material shows good self-cleaning properties under actual use conditions, and therefore, it has greater practical use value than super hydrophobic coatings in the field of self-cleaning coatings. Existing inorganic coatings are mainly prepared by PVD, CVD, sol-gel method and other methods. PVD and CVD methods involve special equipment and vacuum environment, and the preparation area of ​​TiO2 coatings is greatly limited, and the preparation cost is high. The sol-gel method has low cost and is suitable for large-area preparation, but generally requires high-temperature treatment. Although it is possible to prepare a coating that forms a film at room temperature by adding titanium sol, silica sol, etc., such coatings have poor adhesion. In addition, there is an inherent low adhesion problem between inorganic coatings and organic substrates, and TiO2 coatings cannot be combined with existing organic coating systems. The characteristics of the preparation method of inorganic coatings and the inherent characteristics of inorganic coatings determine that their actual application will be limited, and they cannot be used on large outdoor surfaces.

[0003] Therefore, there is an urgent need to provide a self-cleaning coating with good adhesion and excellent self-cleaning properties. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention develops a uniform coating on photovoltaic cover glass by synthesizing SiO2-TiO2 nanoparticles of different particle sizes, so that it has excellent self-cleaning properties, thermal stability, anti-fouling performance and good chemical and mechanical properties.

[0005] According to a first aspect of the present invention, a self-cleaning coating is provided, wherein raw materials for preparing the self-cleaning coating include TiO2 nanoparticles, SiO2 sol and polyethylene glycol;

[0006] The raw materials for preparing the TiO2 nanoparticles include titanyl sulfate;

[0007] The raw materials for preparing the SiO2 sol include ethyl orthosilicate.

[0008] According to the embodiments of the first aspect of the present invention, there are at least the following beneficial effects:

[0009] The present invention uses ethylene glycol to control the particle size of TiO2 nanoparticles, thereby preparing nano-scale SiO2-TiO2 particles to improve light transmittance and film hardness, thereby achieving excellent power generation efficiency. The addition of ethylene glycol and TiO2 for inorganic-organic composite can also improve the adhesion of the SiO2-TiO2 antifouling coating.

[0010] According to some embodiments of the present invention, the raw materials for preparing the TiO2 nanoparticles further include aniline and sodium fluoride.

[0011] The addition of sodium fluoride not only improves the surface structure of titanium dioxide, but also enhances its dispersibility and effectively inhibits the agglomeration phenomenon that occurs during the heat treatment process. The small particle size and large specific surface area obtained make it exhibit excellent activity in the photocatalytic reaction, which is beneficial to improve the photocatalytic degradation efficiency of titanium dioxide. The introduction of aniline can improve the crystal structure of titanium dioxide, so that it forms a tighter lattice structure during high-temperature sintering. Aniline combined with sodium fluoride can improve the stability of TiO2 in long-term use and reduce the performance degradation of the catalyst under high temperature or strong light irradiation. Aniline molecules can form Ti-OF bonds with the surface of TiO2. The interaction between the two may make the surface of TiO2 more stable, not only enhancing its heat resistance, but also improving the antioxidant ability of TiO2 under high temperature conditions.

[0012] According to some embodiments of the present invention, the raw materials for preparing the SiO2 sol also include a catalyst and a solvent.

[0013] According to some embodiments of the present invention, the catalyst includes at least one of hydrochloric acid, phosphoric acid and sulfuric acid.

[0014] According to some embodiments of the present invention, the solvent includes at least one of ethanol, methanol and isopropanol.

[0015] According to some embodiments of the present invention, the raw materials for preparing the TiO2 nanoparticles further include: ethylene glycol and n-propanol.

[0016] According to some embodiments of the present invention, the TiO2 nanoparticles include the following components: a catalyst, titanyl sulfate, ethylene glycol, and n-propanol.

[0017] According to some embodiments of the present invention, the self-cleaning coating further comprises polyethylene glycol.

[0018] According to some embodiments of the present invention, the SiO2 sol includes the following components: tetraethyl orthosilicate, ethanol and hydrochloric acid.

[0019] According to a second aspect of the present invention, a method for preparing a self-cleaning coating is provided, comprising the following steps: mixing TiO2 nanoparticles and SiO2 sol and then mixing with polyethylene glycol to obtain a sol solution of the self-cleaning coating.

[0020] According to some embodiments of the present invention, the self-cleaning coating comprises the following components in parts by weight: 0.1-5 parts of a catalyst, 45-90 parts of tetraethyl orthosilicate, 20-45 parts of titanyl sulfate, 10-25 parts of polyethylene glycol, 25-55 parts of ethylene glycol, and 55-90 parts of n-propanol.

[0021] According to some embodiments of the present invention, the weight ratio of the TiO2 nanoparticles to the SiO2 sol is 1:15-20.

[0022] According to some embodiments of the present invention, the TiO2 nanoparticles and SiO2 sol are mixed for 3 to 5 hours.

[0023] According to some embodiments of the present invention, the method for preparing TiO2 nanoparticles includes: mixing a titanium source and water, heating them for reaction, and then removing impurities.

[0024] According to some embodiments of the present invention, the temperature of the heating reaction is 160-180° C.; the temperature of the heating reaction is 5-7 hours.

[0025] According to some embodiments of the present invention, the impurity removal step includes: centrifuging the solution obtained after the reaction and washing it with a polar solvent, post-treating the supernatant, vacuum drying it at 80-90°C for 6-7h, and crushing the dried particles to obtain highly crystalline TiO2 nanoparticles.

[0026] According to some embodiments of the present invention, the method for preparing the SiO2 sol includes: hydrolyzing a silicon source and then polycondensing it.

[0027] According to the third aspect of the present invention, the application of self-cleaning coating in solar photovoltaic glass coating is proposed.

[0028] According to some embodiments of the present invention, the step of coating the solar photovoltaic glass includes immersion coating the solar photovoltaic glass followed by drying and heat treatment.

[0029] According to some embodiments of the present invention, the solar photovoltaic glass is pre-treated solar photovoltaic glass.

[0030] According to some embodiments of the present invention, the pre-treatment includes placing the solar photovoltaic glass in an ultrasonic cleaning machine and drying it after cleaning.

[0031] According to some embodiments of the present invention, the immersion coating step includes: immersing the solar photovoltaic glass into the sol solution and then pulling it. DETAILED DESCRIPTION

[0032] The embodiments of the present invention are described in detail below, and the examples of the embodiments are shown, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below by reference are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention. The materials, reagents, etc. used in the embodiments, if not otherwise specified, can all be reagents and materials obtained from commercial sources.

[0033] Example 1

[0034] This embodiment provides a self-cleaning coating and coated glass, specifically:

[0035] S1. Add 56 ml of ethylene glycol (EG, 99.5%) to 50 ml of n-propanol, mix continuously for 30 min by mechanical stirring, and place the mixture in an ice bath at a temperature of -10°C;

[0036] S2. 15 ml of titanium oxysulfate was dropped into the previous S1 mixture, the mixture was mechanically stirred for 30 minutes, 5 ml of deionized water was added, and after stirring for 30 minutes, the solution was transferred to an autoclave and subjected to solvent thermal synthesis at 180°C for 6 hours. At the same time, the solution was centrifuged and washed with a polar solvent, and then the supernatant was treated and vacuum dried at 80°C for 6 hours. The dried particles were crushed to obtain highly crystalline TiO2 nanoparticles;

[0037] S3. 120 ml of ethanol, 0.3 ml of hydrochloric acid and 15 ml of ethyl orthosilicate were mixed and stirred for 4 h to a pH value of 2.4, and deionized water was slowly added dropwise to the mixed solution to obtain SiO2 sol;

[0038] S4. Disperse 1 g of synthesized TiO2 nanoparticles in 20 g of SiO2 sol and stir for 3 h, then add polyethylene glycol-1000 (the weight ratio of SiO2-TiO2 sol to polyethylene glycol-1000 is 5:9) to obtain a highly stable antifouling coating solution.

[0039] The preparation method of coated glass is:

[0040] S5. Place the glass in an ultrasonic cleaner for 0.5 h, then place it in an oven at 60°C for 1 h to dry; use a dip coater to dip the dried glass into the antifouling coating solution at a speed of 1000 μm / s. After immersion for 10 min, pull up the coated glass at the same speed as the immersion and cure it in an oven at 180°C for 0.5 h. Finally, anneal the coated glass at 400°C for 10 min to obtain self-cleaning antifouling properties.

[0041] Example 2

[0042] This embodiment provides a self-cleaning coating and coated glass, specifically:

[0043] S1. Add 28 ml of ethylene glycol (EG, 99.5%) to 50 ml of n-propanol, mix continuously for 30 min by mechanical stirring, and place the mixture in an ice bath at a temperature of -10°C;

[0044] S2. 15 ml of titanium oxysulfate was dropped into the previous mixture, the mixture was mechanically stirred for 30 minutes, 5 ml of deionized water was added, and stirred for 30 minutes, then the solution was transferred to an autoclave, and solvothermal synthesis was carried out at 180°C for 6 hours, and the solution was centrifuged and washed with a polar solvent, and then the supernatant was treated and vacuum dried at 80°C for 6 hours, and the dried particles were crushed to obtain highly crystalline TiO2 nanoparticles;

[0045] S3. 120 ml of ethanol, 0.3 ml of hydrochloric acid and 15 ml of ethyl orthosilicate were mixed and stirred for 4 h to a pH value of 2.4, and deionized water was slowly added dropwise to the mixed solution to obtain SiO2 sol;

[0046] S4. Disperse 1 g of synthesized TiO2 nanoparticles in 20 g of SiO2 sol and stir for 3 h, then add polyethylene glycol-1000 (the weight ratio of SiO2-TiO2 sol to polyethylene glycol-1000 is 5:9) to obtain a highly stable antifouling coating solution.

[0047] The preparation method of coated glass is:

[0048] S5. Place the glass in an ultrasonic cleaner for 0.5 h, then place it in an oven at 60°C for 1 h to dry; use a dip coater to dip the dried glass into the antifouling coating solution at a speed of 1000 μm / s. After immersion for 10 min, pull up the coated glass at the same speed as the immersion and cure it in an oven at 180°C for 0.5 h. Finally, anneal the coated glass at 400°C for 10 min to obtain self-cleaning antifouling properties.

[0049] Example 3

[0050] This embodiment provides a self-cleaning coating and coated glass, specifically:

[0051] S1. Add 28 ml of ethylene glycol (EG, 99.5%) to 50 ml of n-propanol, mix continuously for 30 min by mechanical stirring, and place the mixture in an ice bath at a temperature of -10°C;

[0052] S2. 15 ml of titanium oxysulfate was dropped into the previous mixture, the mixture was mechanically stirred for 30 minutes, 5 ml of deionized water, aniline and sodium fluoride were added and stirred for 30 minutes, then the solution was transferred to an autoclave and subjected to solvent thermal synthesis at 180°C for 6 hours, and the solution was centrifuged and washed with a polar solvent, and then the supernatant was treated and vacuum dried at 80°C for 6 hours, and the dried particles were crushed to obtain highly crystalline TiO2 nanoparticles;

[0053] S3. 120 ml of ethanol, 0.3 ml of hydrochloric acid and 15 ml of ethyl orthosilicate were mixed and stirred for 4 h to a pH value of 2.4, and deionized water was slowly added dropwise to the mixed solution to obtain SiO2 sol;

[0054] S4. Disperse 1 g of synthesized TiO2 nanoparticles in 20 g of SiO2 sol and stir for 3 h, then add polyethylene glycol-1000 (the weight ratio of SiO2-TiO2 sol to polyethylene glycol-1000 is 5:9) to obtain a highly stable antifouling coating solution.

[0055] The preparation method of coated glass is:

[0056] S5. Place the glass in an ultrasonic cleaner for 0.5 h, then place it in an oven at 60°C for 1 h to dry; use a dip coater to dip the dried glass into the antifouling coating solution at a speed of 1000 μm / s. After immersion for 10 min, pull up the coated glass at the same speed as the immersion and cure it in an oven at 180°C for 0.5 h. Finally, anneal the coated glass at 400°C for 10 min to obtain self-cleaning antifouling properties.

[0057] Comparative Example 1

[0058] This comparative example provides a self-cleaning coating and coated glass, specifically:

[0059] S1. Stir 0 ml of ethylene glycol (EG, 99.5%) for 30 min, and place the mixture in an ice bath at -10 °C;

[0060] S2. 15 ml of titanium oxysulfate was dropped into the previous mixture, the mixture was mechanically stirred for 30 minutes, 5 ml of deionized water was added, and stirred for 30 minutes, then the solution was transferred to an autoclave, and solvothermal synthesis was carried out at 180°C for 6 hours, and the solution was centrifuged and washed with a polar solvent, and then the supernatant was treated and vacuum dried at 80°C for 6 hours, and the dried particles were crushed to obtain highly crystalline TiO2 nanoparticles;

[0061] S3. 120 ml of ethanol, 0.3 ml of hydrochloric acid and 15 ml of ethyl orthosilicate were mixed and stirred for 4 h to a pH value of 2.4, and deionized water was slowly added dropwise to the mixed solution to obtain SiO2 sol;

[0062] S4. Disperse 1 g of synthesized TiO2 nanoparticles in 20 g of SiO2 sol and stir for 3 h, then add polyethylene glycol-1000 (the weight ratio of SiO2-TiO2 sol to polyethylene glycol-1000 is 5:9) to obtain a highly stable antifouling coating solution.

[0063] The preparation method of coated glass is:

[0064] S5. Place the glass in an ultrasonic cleaner for 0.5 h, then place it in an oven at 60°C for 1 h to dry; use a dip coater to dip the dried glass into the antifouling coating solution at a speed of 1000 μm / s. After immersion for 10 min, pull up the coated glass at the same speed as the immersion and cure it in an oven at 180°C for 0.5 h. Finally, anneal the coated glass at 400°C for 10 min to obtain self-cleaning antifouling properties.

[0065] Test Example 1

[0066] In this test example, the performance of the antireflection films obtained in the examples and comparative examples was tested. The test results of the hydrophobic performance and transmittance are shown in Table 1.

[0067] Table 1 Transmittance and water contact angle of antifouling coating under sunlight at different time in Examples and Comparative Examples

[0068]

[0069] 1d, 15d, 30d, 45d, and 90d are the test results of the coatings placed outdoors for different days. For example, 96.7% and 1.5° in the table respectively represent that the transmittance of Example 1 is 96.7% and the contact angle is 1.5° after being placed outdoors for 1 day.

[0070] The SiO2-TiO2 antifouling coatings synthesized with ethylene glycol at concentrations of Example 1 (1 mol / L ethylene glycol), Example 2 (0.5 mol / L ethylene glycol) and Comparative Example 1 (0 mol / L ethylene glycol) were divided into Example 1 prepared with nano-sized particles in the wavelength range of 380-1100 nm, and Example 1, which was prepared with nano-sized particles, had only 1.9% transmission loss under 90 days of outdoor testing. In Example 3, aniline combined with sodium fluoride can improve the stability of TiO2 in long-term use and reduce the performance degradation of the catalyst under high temperature or strong light irradiation. Example 3 had only 1.1% transmission loss under 90 days of outdoor testing.

[0071] The transmission loss of the glass in Comparative Example 1 is 6.2%. The lower transmission loss of Example 1 is due to its average particle size of 7nm, which leads to lower reflection loss. Example 2 also leads to a 3% transmission loss due to its higher average particle size (14nm). In addition, it can be seen that Examples 1 and 2 can still maintain super hydrophilic properties under 90d outdoor testing, making their surfaces have good self-cleaning properties, while the hydrophilic properties of Comparative Example 1 are greatly lost, indicating that the addition of ethylene glycol can improve the self-cleaning properties of the photocatalytic coating.

[0072] In addition, the introduction of ethylene glycol also improves the transmittance of the film layer, but due to its long carbon chain, the steric hindrance is large during the condensation process after hydrolysis, and excessive addition is not easy to react, so its dosage needs to be controlled. Therefore, the relationship between the amount of ethylene glycol added and the transmittance of the film layer was explored. When the amount of ethylene glycol added increased between 0 and 1 mol / L, the transmittance of the film layer in the wavelength range of 400 to 800 nm increased with the increase in the amount of addition. However, as the amount of ethylene glycol added further increased, the transmittance of the film layer decreased. Appropriately increasing the content of ethylene glycol is conducive to its complete reaction with the silicon dioxide in the system (adding ethylene glycol to react with silicon dioxide in S2). At this time, the particle size increases with the increase of ethylene glycol content. After the film layer is formed, it helps to form a better porosity and increase the transmittance. However, if the ethylene glycol content is excessively increased, the unreacted ethylene glycol will remain in the system. Due to the high boiling point of ethylene glycol, it is difficult to remove during the baking process, which reduces the porosity of the film and reduces the transmittance of the film.

[0073] Since the nanometer size of SiO2-TiO2 after the addition of ethylene glycol reduces the reflection loss and the effective refractive index, and the nanometer size particles minimize the effective refractive index, the best optical performance is obtained in Example 1. The average transmittance in the wavelength region of 380-1100nm is observed to be 96.7%, while the average transmittance of Comparative Example 1 is 93.7%. Considering the key optical properties of the coating particles synthesized at 1 mol / LEG, it is determined that it has ideal antifouling coating properties due to its nanometer size, and Example 1 is determined to be the best antifouling coating among the three coatings.

[0074] The photocatalytic degradation activity of comparative example 1 is relatively weak, and the degradation rate of rhodamine B (Rh-B) dye is only about 30% within 150 minutes. However, after the SiO2-TiO2 antifouling coating is combined with ethylene glycol, the catalytic activity is significantly improved within the same time. The degradation efficiency of Example 3 is 60%, while the degradation efficiency of Example 2 is 75%. This may be because the specific surface area of ​​Example 2 is higher than that of Example 3. Since the surface area of ​​the high specific surface area material of Example 2 is larger, more molecules or ions can be adsorbed, thereby providing more reaction sites. The most important discovery is that Example 1 exhibits a stronger catalytic activity than Example 3, with a degradation rate of nearly 93%, while the degradation efficiency of Example 3 is 95%. The combination of aniline and sodium fluoride not only stabilizes TiO2 in structure, but also optimizes its photocatalytic properties. Among them, aniline improves electron transport and carrier separation, and sodium fluoride reduces the degradation rate of the photocatalyst by optimizing the surface properties. The synergistic effect of the two enhances the overall photocatalytic efficiency of the coating, thereby improving the degradation rate of Rh-B dye.

[0075] Based on the excellent optoelectronic and structural properties of nanocomposites, it has attracted great attention from scientific researchers. After the Z-type heterojunction is compounded with the SiO2-TiO2 coating, the photocurrent response is significantly improved. The light-generated holes accumulated in the valence band of the Z-type heterojunction are combined with the photogenerated electrons transmitted from the conduction band of TiO2 to the Z-type heterojunction, resulting in a significant accumulation of holes in the valence band of TiO2. These holes have strong oxidizing properties and can therefore react immediately with pollutants to achieve degradation targets. Therefore, the present invention studies the synergistic ability of the Z-type heterojunction and Example 1. First, a certain amount of thiourea is placed in a sealed crucible and heated to obtain a corresponding sample, which is then mixed and stirred with Example 1. Finally, a certain amount of Rh-B solution is added to the mixed solution for degradation activity test. It can be concluded that under light, Example 1 and the Z-type heterojunction can decompose 99% of Rh-B in only 40 minutes, and its catalytic activity is much higher than that of Example 1. The latter can only decompose about 60% of Rh-B in the same time. It may be that Example 1 has a lower internal specific surface area than the heterojunction composite and cannot provide more active sites.

[0076] In order to demonstrate the practical applicability of Example 1, the degradation of tetracycline hydrochloride (TC-HCl) under the synergistic system of Example 1 and Z-type heterojunction was tested. The results showed that when exposed to simulated sunlight, the synergistic system of Example 1 and Z-type heterojunction could decompose about 80% of TC-HCl in less than 60 minutes. This result shows that the synergistic system of Example 1 and Z-type heterojunction is superior for degrading challenging organic compounds such as tetracycline hydrochloride.

[0077] The assembled modules were placed outdoors to observe the self-cleaning performance of the antifouling coating. As the pollution gradually increased, after 60 days, the pollution loss of the module of comparative example 1 was 9.2%, while the pollution loss of the module of embodiment 1 was 0.5%. It can be concluded that the pollution loss of the coated module was 8.7% lower than that of the uncoated module. Compared with the module of comparative example 1, the antifouling coating of embodiment 1 on the photovoltaic module can degrade organic pollutants to a large extent, bind them together, reduce the adhesion of dust on the micromodule, and reduce pollution loss.

[0078] Table 2 Adhesion test results of examples and comparative examples

[0079] Different types of coatings Adhesion Example 1 Level 0 Example 2 Level 0 Comparative Example 1 Level 1

[0080] The mechanical stability of the antifouling coating in Table 2 was tested for scratch and adhesion stability by ASTM3363 and ASTM3359-17. The coating has excellent pencil hardness (5H) and adhesion by the 4B cross-cut tape test. The coating is very stable and can withstand the wear and tear during regular cleaning of photovoltaic modules. The weather stability of the antifouling coating was tested using the IEC61646 standard, including wet freeze test, wet heat test and thermal cycle test, and the coating was tested for more than 1500 hours. After the samples were tested for light transmittance, photo-induced super hydrophilicity and photocatalytic activity, as well as weather stability, it was found that the coating was stable, the transmittance did not decrease, and it had good photo-induced super hydrophilicity and photocatalytic activity.

[0081] Coating adhesion test method: According to GB9286, the coating adhesion is tested using the grid method. The test steps are as follows: ① Use a paper cutter to draw vertical cross parallel cutting lines with a spacing of 1mm on the coated slide, ten horizontal and vertical lines; ② Use transparent tape to stick the test area of ​​the coating, and then rub the test area back and forth with your fingers to make the tape and the coating in good contact; ③ Evenly tear off the tape to observe the damage of the coating. The coating in the test area is still intact, which is level 0, the damaged area is 5% is level 1, and the damaged area is 5% to 15% is level 2.

[0082] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A self-cleaning coating, characterized in that: The raw materials for preparing the self-cleaning coating include TiO2 nanoparticles, SiO2 sol and polyethylene glycol; The raw materials for preparing the TiO2 nanoparticles include titanyl sulfate; The raw materials for preparing the SiO2 sol include ethyl orthosilicate.

2. The self-cleaning coating according to claim 1, characterized in that The raw materials for preparing the TiO2 nanoparticles also include aniline and sodium fluoride.

3. A method for preparing a self-cleaning coating as claimed in any one of claims 1 or 2, characterized in that: The following steps are involved: The TiO2 nanoparticles and SiO2 sol are mixed and then mixed with polyethylene glycol to react to obtain a sol solution of a self-cleaning coating.

4. The preparation method according to claim 3, characterized in that: The method for preparing the TiO2 nanoparticles comprises: mixing a titanium source and water, heating the mixture for reaction, and then removing impurities.

5. The preparation method according to claim 4, characterized in that: The temperature of the heating reaction is 160-180° C.; the temperature of the heating reaction is 5-7 hours.

6. The preparation method according to claim 3, characterized in that: The method for preparing the TiO2 nanoparticles comprises: mixing a titanium source and water, heating them for reaction, and then adding polyaniline and sodium fluoride to mix.

7. The preparation method according to claim 3, characterized in that: The preparation method of the SiO2 sol comprises: hydrolyzing a silicon source and then polycondensing it.

8. Use of the self-cleaning coating as claimed in claim 1 or 2 in solar photovoltaic glass coating.

9. The use according to claim 8, characterized in that: The step of coating the solar photovoltaic glass comprises: dipping and coating the solar photovoltaic glass, followed by drying and heat treatment.

10. The use according to claim 8, characterized in that: The immersion coating step includes: immersing the solar photovoltaic glass into the sol solution and then pulling it up.